The Position of Stocks as a Place for Speculation in the Ulama's Perspective - Muhamad Izazi Nurjaman; Dea Dahlia; Nur Fadhilah Novianti (Journal of Islamic Law and Legal Studies, 2024)
Share transactions in the sharia capital market must comply with sharia principles. The aim of this research is to analyze the position of stocks that are used as an arena for speculation in the views of scholars, both classical scholars and contemporary scholars. This research is library research with a descriptive analysis method using a normative juridical approach. The research data analysis was carried out through three mechanisms, namely data reduction, data presentation and drawing conclusions. The results of the research show that Based on the discussion above, it shows that in the view of the ulama it has been explained that speculative activities, Riba, Gharar and Maysir (gambling) have been prohibited by Islamic law which was issued as a regulation. One of them is setting a minimum holding period for shares. With these restrictions, shares cannot be traded at any time, so there is little incentive to profit from price changes alone. However, finding the right retention period can be difficult. These restrictions can limit speculation, but also reduce the liquidity of capital market investments. Therefore, it is very possible that a rational investor needs quick liquidity but cannot sell shares because the required minimum holding period has not been met.